The degree of Islamic education teachers’ practice of teaching strategies that develop creative thinking skills among students of the last cycle of basic education in the capital Sana’a - Al-Afad, Abdullah Ali Hadi (Journal of Curriculum and Teaching Methodology, 2022)
The study aimed to reveal the degree to which Islamic education teachers and female teachers practice teaching strategies that develop creative thinking skills among students of the last cycle of basic education in the capital Sana’a، and to find out whether there are statistically significant differences between the average scores of the study members in their practice of teaching strategies that develop thinking skills. The creativity of the students of the last cycle of basic education in the capital Sana’a، according to the variables (specialization، gender، qualification، and experience). The study used the descriptive survey method، and the observation card was adopted as a tool for it. A set of results، the most important of which are: The degree to which Islamic education teachers and female teachers practice teaching strategies that develop creative thinking skills among students of the last cycle of basic education in the capital Sana’a was “weak” with an arithmetic average of (2.25). The study also showed that there were no statistically significant differences at the level (0.05) between the average degree of practice of Islamic education teachers and their female teachers of teaching strategies that develop creative thinking skills due to the variable of specialization (educational - non-educational) and the qualification variable (bachelor - diploma). Statistical at the level (0.05) between the averages of the degree of Islamic education teachers’ practice of teaching strategies that develop creative thinking skills due to the gender variable (male-female) in the field of fluency skills in the direction of females، and there are no statistically significant differences in the skills of originality and flexibility.